"Survey of Intestinal Parasitic Infection in Leukemic Children and Evaluation of their Serum Immunoglobulins" - MJ Gharavi; F Ashraf; P Vosough; MB Rokni (Tehran University of Medical Sciences, 2003)
Infection is one of the cardinal difficulties in the children with acute leukemia and is the leading cause of mortality among them. The prevalence of infection in these patients has several reasons including usage of cytotoxic agents, corticosteriods, broad consumption of antibiotics, duration of confinement in hospital, defective of cellular and humoral Immunity, neutropenia and dysfunction of neutrophils. Despite the fact that intestinal parasitic infection is a rather frequent finding and a health problem in developing countries, in our experience the incidence of helminthic and protozoa infections among children with leukemia was uncommon. Totally 141 patients with leukemia and 70 cases of control group were examined in a period of 12 months, which 40% and 2.8% of former and latter groups, had intestinal pathogen and non-pathogen parasites, respectively. When we compared the frequency of parasitic infection in the control group with the leukemic children, we found no significant difference. It is speculated that parasitic infections may uncommon in these children for numerous reasons such as immunologic and pharmacologic parameters.